Argamassa Reforçada com Armadura Difusa de Aço - Nascimbeni, José Eduardo Fairbanks (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1990)
The aim is to get data for registering the behavior of steel fibres reinforced mortar. Features testing methods, results and conclusions about studies carried on pieces of armed mortar. Some theoretical questions about the faults in cementitious materials and the effect of fibres in brittle matrices were also studied. It is clear that it does exist the technological viability in its use. This text is written in Portuguese